Analisis Rantai Nilai (Value Chain) pada Usaha Rumah Karawo Kota Gorontalo - Tri Sukma Pulukadang; Zulkifli Bokiu; Ayu Rakhma Wuryandini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out how the Value Chain Practices in the Karawo Home Business, Gorontalo City. This research uses a qualitative method with a descriptive approach and uses data collection techniques using primary data obtained directly from observation, interviews and documentation. The results of this research show that there are two activities that are carried out well in the Karawo House Business in Gorontalo City, namely primary and supporting activities. Primary activities include inbound logistics consisting of receiving and storing raw materials, scheduling vehicles via J&E or cargo. The operation starts from designing the motif, making cuts on the fabric, finally embroidering and sewing the clothes. Outbound logistics consists of product collection, product storage to the Rumah Karawo boutique. However, Rumah Karawo does not have a distributor, so products are sold directly to customers. Marketing and sales, namely by utilizing relationships, fashion shows, marketing and sales through online and offline, advertising and promotions. As well as providing service to customers. Supporting activities include Company Infrastructure which includes general management, planning for the development of Rumah Karawo, and finances at Rumah Karawo which still need to be improved. Human Resources Management is quite good but does not provide special training for workers. The technology used is still simple except for designing motifs. as well as Procurement/purchase of raw materials and karawo equipment.